Learning to Be Employable Through Volunteering: A Qualitative Study on the Development of Employability Capital of Young People - Giancaspro, Maria Luisa; Manuti, Amelia (Frontiers in Psychology, 2021)
Over the last decades, consistent research showed that voluntary work could be considered as a tool for professional development and concrete employment: volunteering could be either experienced as a desire to improve career opportunities or to acquire new skills. The study aimed to investigate voluntary work as a context of informal and non-formal workplace learning and vocational guidance, useful to develop skills and abilities, namely the capital of personal and social resources, that could promote future employability. Participants were 38 young volunteers who experienced the Universal Civil Service, a national Italian program addressed to young people aged up to 28 years, giving them both the opportunity to engage in social activities useful for the community and have the first contact with a working context. In line with the objectives of the study, participants were invited to describe their volunteering experience in a diary, highlighting if and to what extent this context contributed to enhancing their employability capital, namely the asset of skills, knowledge, and networks acquired, that they could transfer to a future professional domain. The narrative data collected were examined through diatextual analysis, a specific address of discourse analysis designed to catch the relationship between enunciators, text, and context of the talk. This qualitative analysis allowed us to investigate the meanings young people attributed to these activities. In light of these results, the paper contributed to investigate volunteers’ perceptions about the conditions that could best foster this specific kind of workplace informal and non-formal learning and at proposing a qualitative perspective on the analysis of the employability capital they developed.